1998
DOI: 10.1038/sj.gt.3300728
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell-specific transgene expression prevents liver toxicity of the adeno-HSVtk/GCV approach

Abstract: Treatment of colorectal liver metastases with the bystander effect. Moreover, treatment of subcutaneous HSVtk/GCV approach and adenoviral vectors is highly tumors in SCID mice with Ad.CEA-tk led to a several-fold toxic. We present a nontoxic alternative using the cell typereduction of tumor growth, and tail vein injection of a high specific CEA promoter instead of the widely used hCMV dose of Ad.CEA-tk caused no side-effects in the liver. The immediate-early promoter to drive tk gene expression in CMV promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…The CEA promoter can be applied to diverse cancers in which this gene is overexpressed, such as gastric carcinoma [23] and colorectal cancer [24]. Adenoviral vectors carrying CEA promoterdriven therapeutic genes were able to mediate targeted expression, tumor regression and prolonged survival in CEA + tumor-bearing mice [25], with minimal liver toxicity [26]. Because AFP and CEA are used as serum diagnostic markers in several carcinomas [27,28], employing these promoters as targets would be supported in expression-positive carcinomas.…”
Section: Transcriptional Targetingmentioning
confidence: 99%
“…The CEA promoter can be applied to diverse cancers in which this gene is overexpressed, such as gastric carcinoma [23] and colorectal cancer [24]. Adenoviral vectors carrying CEA promoterdriven therapeutic genes were able to mediate targeted expression, tumor regression and prolonged survival in CEA + tumor-bearing mice [25], with minimal liver toxicity [26]. Because AFP and CEA are used as serum diagnostic markers in several carcinomas [27,28], employing these promoters as targets would be supported in expression-positive carcinomas.…”
Section: Transcriptional Targetingmentioning
confidence: 99%
“…37 It has been shown that Ad virus infection of cells can cause cell cycle dysregulation, which is characterized by a G2 -like cell cycle arrest and deregulated expression of cyclins A, B1, D, and cdk p34cdc2 protein levels. 59,72 However, the cell cycle disturbances observed in our experiments were clearly due to the overexpression of p16 and not the adenoviral infection itself because irrespective of the genomic status of p16, p53, p21, or bax of tumor cells, infection with various control vectors did not induce significant cell cycle disturbances and apoptosis.…”
Section: Discussionmentioning
confidence: 62%
“…17,20,30 Several tissue-specific promoters have been investigated for their ability to mitigate the liver toxicity associated with TK-mediated 'suicide' gene therapy. 31,32 In the present study, we reasoned that the OBHRE promoter would be suitable for this purpose due to its low basal activity in normal tissue. We compared the in vivo toxicity of the Ad.HRETK and Ad.CMVTK vectors.…”
Section: Hre-mediated Tumour Targetingmentioning
confidence: 92%